LANGUAGE ACQUISITION OF CHILDREN AGE FOUR-YEAR-OLD AT THE PHONOLOGICAL LEVEL - Kartika, Novi (Fakultas Ilmu Budaya and LPPM Universitas Sebelas April, 2024)
The writer analyzes the language acquisition of children aged four years old at the phonological level. The main focus of this research is that the writer wants to identify phonological aspects in the language of four-year-old children and the extent to which four-year-old children have achieved language skills. This study focused on a child named Restu Fauzi using an approach from the branch of micro linguistics, namely phonology. The researcher uses a descriptive qualitative method, where this descriptive research aims to describe the phenomena that are the focus of the author factually and accurately regarding language acquisition and is carried out by recording and note-taking techniques using the observation method to get a clear picture of the activities carried out by Restu. This research is done by paying attention to the utterances of every activity that Restu does in his daily life and there is also an interview process, where he directly dialogues with Restu. The results of the research are then translated through a detailed description of the words regarding the results of the utterances and the vowel sounds [a], [i], [u], [e], [o], and the mention of the resulting consonant sounds, by Restu, and to find out Restu's language achievement.